HUBUNGAN KEBIASAAN SARAPAN, ASUPAN ENERGI DARI SNACKING, DAN INTENSITAS MENGGUNAKAN GADGET DENGAN GIZI LEBIH PADA ANAK SD DI RW 02 CIPEDAK - Lativa Nur Aini, (2021)
Overweight is one of the high problems in elementary school children. Nutrition is more influenced by the habit of children not eating breakfast, the habit of snacking on high-calorie foods, the intensity of the children using gadgets that make children's physical activity low, genetic factors, and also other environmental factors. Overweight in children can cause problems. The impact if a child overweight among other things trigger depression, risk of obesity as an adult, can increase the risk of type 2 diabetes mellitus and heart disease. In Indonesia, the prevalence of overweight in children aged 5-12 years reaches 18.8%. The study was to determine the relationship between breakfast habits, energy intake from snacking, and the intensity of using gadgets with the incidence of overweight in elementary school children in RW 02 Cipedak in 2021. This study used a cross sectional method. The sample on this research totaled 71 respondents used purposive sampling technique. Bivariate analysis using the chi-square test. The results showed that there was a relationship between breakfast habits and the incidence of overweight (p value = 0.015) and there was a relationship between energy intake from snacking and the incidence of overweight (p value = 0.00). However, there was no relationship between the intensity of using gadgets and the incidence of overweight (p value = 0.866).